Empowering Empowering Health Cadres in Rural Communities for Heart Attack Prevention and First Aid Response - Dg Mangemba; Dian Kurniasari Yowono (Jurnal Pengabdian Masyarakat Lentora, 2026)
The prevalence of heart disease cases in Awu Village remains quite high, with 18 cases recorded in the past year alone. Death in cardiac arrest cases can occur because health workers are unable to treat victims in the emergency phase. Appropriate handling measures in handling emergency cases of cardiac arrest are not only health service workers but also lay people, including community health cadres in Awu Village who serve as first responders. Efforts that can be made to address this problem include conducting community service activities in the form of providing education about heart attacks, basic life support training, and training in selecting and processing healthy food ingredients. The purpose of this PkM activity is to increase knowledge about heart disease, improve cadre skills related to basic life support skills, and improve skills in selecting and processing healthy food ingredients. The methods used in this community service activity were lectures and Q&A sessions using PPT media and leaflets, combined with hands-on basic life support practice. A one-day structured training (6 hours) was conducted, including pre- and post-tests to measure knowledge gain. The target of this activity is cadres and the community in Awu Village, North Luwuk District, Banggai Regency, totaling 40 people, which was carried out on July 30, 2025. The results showed an increase in the average knowledge and skills score from 43.50 (pre-test) to 91.00 (post-test) out of a maximum score of 100, indicating a significant improvement (p < 0.05). This activity is expected to be a follow-up activity for the Awu village to carry out continuous education by collaborating with the local health center. The output of this PKM activity is the publication of articles in scientific journals, activity videos, online news and IPR leaflets.